Uso de água residuária de origem doméstica no cultivo da pimenta malagueta na Chapada do Apodi-RN - Dutra, Ian Crisóstomo Bezerra (2013)
The agricultural use of treated domestic wastewater is an alternative in the face of water scarcity and environmental degradation in the semiarid region. The study aimed to analyze the effects of the application of domestic wastewater in the production system of chilli pepper. For this purpose, an experimental area of 744 m2 was mounted on rural community Milagres in Apodi-RN, comprising a primary effluent treatment system and a drip irrigation automated. The chili pepper was planted in Cambisol with spacing of 1.0 m between rows of plants per 0.30 m between plants. In conducting the experiment were used 25 plots, each parcel occupied 12.5 m2. The treatments were T1 - 100% of domestic primary wastewater application (ARP) and 0% water supply (AA), T2 - 75% of ARP and 25% of AA, T3 - 50% of ARP and 50% of AA, T4 - 25% of ARP and 75% of AA and T5 - 0% of ARP and 100% of AA. The experimental design was randomized blocks with five replications. During the experimental period, samples were collected from wastewater and supply for physical-chemical and microbiological analyses, soil samples at depths of 0 to 0.20 m, 0.20 to 0.40 m, 0.40 to 0.60 m for physical-chemical analyses and samples of the fruits of chilli pepper to determine productivity and microbiological risk. The results indicated that the Treatment system presented, during the trial period, good performance with greater than 80% removal of turbidity, total coliform, fecal coliform, biochemical oxygen demand, chemical oxygen demand, suspended solids, phosphorus, oil and grease and nitrate; on cambissolo the pH, electrical conductivity of the saturation extract, calcium, magnesium, sodium, potassium, phosphorus, nitrogen and organic matter increased with increasing proportions of primary domestic wastewater in relation to water supply, and treatment T4 was the most suitable for the production of chilli pepper, by minimizing the effects of accumulation and leaching of chemical elements in the soil, higher productivity and lower risk of microbiological agricultural product